ANALISIS FAKTOR YANG BERPENGARUH TERHADAP KEPUASAN KERJA PENILIK PENDIDIKAN NON FORMAL DAN INFORMAL DINAS PENDIDIKAN KABUPATEN SUKOHARJO - -, Mugiyono -; -, Ernawati - (Universitas Slamet Riyadi, 2010)
ABSTRACT Job satisfaction overseers PNFI (Non-Formal and Informal Education), particularly in Â Education Office of Sukoharjo generally still does not meet expectations, due to the results of functional training, emotional intelligence, and performance has not been fully supported. To improve job satisfaction bishops PNFI the improvement and development of the results of functional training, emotional intelligence, and performance necessary to obtain better compliance. This study is a population with 36 respondents bishops PNFI in Â Education Office of Sukoharjo. Data were collected through a questionnaire, while data analysis techniques using Multiple Linear Regression Analysis. The results of this study indicate that (1) the results of functional training has positive and significant impact on job satisfaction PNFI overseers, (2) emotional intelligence and significant positive effect on job satisfaction PNFI overseers, (3) performance and a significant positive effect on job satisfaction PNFI overseers; (4) performance variables have a dominant influence on job satisfaction PNFI inspector. Keywords: results of functional training, emotional intelligence, performance, job satisfaction.